The Influence of Academic Supervision, Communication, and Participatory Decision Making on Teacher Performance with School Climate as Moderator Variable - Dyah Rachmawatie, Agnees; Soesanto, Soesanto; Hudallah, Noor; Pramono, Suwito Eko; Yulianto, Arief (Universitas Negeri Semarang, 2025)
Teacher performance refers to the success of teachers in creating a directed and effective learning process. Factors that influence teacher performance include academic supervision, communication, participatory decision-making, and school climate. In practice, supervision is not always implemented effectively, and communication between principals and teachers does not consistently run harmoniously. This study aims to examine the influence of academic supervision, communication, and participatory decision-making on teacher performance, with school climate as a moderating variable. The research employed a quantitative survey design. Data were collected using questionnaires and documentation. Questionnaires gathered information related to academic supervision, communication, participatory decision-making, and school climate, while documentation was used to obtain Teacher Performance Assessment (PKG) data. The sample consisted of 114 civil servant (PNS) teachers and principals from four public junior high schools in Banyumanik Sub-district, selected using purposive sampling. The findings show that academic supervision, communication, and participatory decision-making each have a significant effect on teacher performance. School climate does not have a direct significant effect on performance, but it strengthens the influence of academic supervision and communication on performance. However, it does not moderate the influence of participatory decision-making. The study recommends providing opportunities for teachers to engage in decision-making and fostering a positive, supportive school climate to improve performance